Performances of the Fibrin Monomer Test for the Exclusion of Pulmonary Embolism in Symptomatic Outpatients - Reber, Guido; Bounameaux, Henri; Perrier, Arnaud; Moerloose, Philippe de (Thrombosis and Haemostasis, 1999)
Many studies have shown that D-dimer determinations can be used for the exclusion of venous thromboembolism in symptomatic outpatients, depending however on the method of D-dimer measurement. Another related assay, the Fibrin Monomer test which measures soluble fibrin levels in plasma by ELISA, is now available.We have evaluated the performances of this assay for the exclusion of pulmonary embolism (PE) in 426 consecutive outpatients presenting at the emergency ward of our institution. Diagnosis of PE was made by D-dimer measurement, compression ultrasonography, lung scintigraphy, venography and pulmonary angiography. With a cut-off of 3 μg/ml, the sensitivity and the negative predictive value were both 100% (95% CI: 97.1-100 and 96.3-100 respectively) and the specificity 33% (95% CI: 25.7-38.1). With 4 μg/ml, the corresponding figures were 98.4 (95% CI: 94.4-99.8), 98.3 (95% CI: 94.1-99.8) and 39% (95% CI: 33.6-44.7) respectively. The prevalence of PE was 30%, the exclusion rates were 23 and 27% for either cut-off. When compared with a reference D-dimer assay (Asserachrom D-Di), a good correlation was observed. In conclusion, this is the first study suggesting the interest of this Fibrin Monomer test to rule out PE; these results, however, need to be confirmed by other studies.